Menggali dan Membangun Keunggulan Kompetitif Melalui Kearifan Lokal Masyarakat Ciptagelar, Sukabumi, Provinsi Jawa Barat - Pranowo, Agus Setyo; Zuniarti, Ida; Mazia, Lia; Windi, Windi; Sambodo, Priyo; Rachman, Nono Arief; Sienifa, Yuhelmis; Isbat, Isbat; Alimin, Ismet; Yusuf, Nanang Qosim; Lasut, Henry (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
Community service activities aim to provide socialization about strategies to achieve competitive advantage for the Ciptagelar Community, Sukabumi, West Java without having to abandon local wisdom and culture that has been strongly adhered to by the Ciptagelar Community. Community Service Activities for the Ciptagelar community aim to increase the role of local wisdom in empowering the community and building competitive advantages at the local level. The service approach is carried out through active collaboration with the local community. Service activities are carried out by means of outreach to explore and recognize local wisdom which is manifested in Ciptagelar in Sukabumi. Active community participation is the main basis in this process, so that increasing local knowledge and skills can make a positive contribution to economic development and sustainability in the area. The results of the service show that through a collaborative approach and community empowerment, the local wisdom of the Ciptagelar community can be integrated into various sectors, including micro and small businesses, tourism and creative industries. Increasing community participation in utilizing Ciptagelar as a local resource can open up new opportunities for sustainable economic development in Sukabumi. This journal provides a practical overview of how community service can be an effective instrument in exploring and building competitive advantages through local wisdom. The implications of this service activity can be a model for developing participatory strategies in utilizing local potential to increase the competitiveness and welfare of communities in various regions.